Analysis and design of intelligence test applications (psychotest) for job applications - Pasaribu, Sutrisno Arianto; Pasaribu, Victor Patar; Hirzi , M Fakrul; Arahman, Hamzah; Halawa , Jerisekiawan (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
In this era of globalization, increasingly fierce competition in the world of work encourages companies to choose employees who not only have high academic qualifications, but also intelligence that matches job demands. Therefore, this research aims to develop and analyze the application of Intelligence Tests (Psychotest) as an effective job application assessment tool. System analysis and design methods are used to design applications that can measure various aspects of intelligence, including verbal, numerical and spatial intelligence. The analysis stage involves an in-depth understanding of the company's needs in assessing applicant intelligence. Meanwhile, the design stage includes the design of an intuitive user interface, an efficient database structure, and a valid and reliable intelligence measurement algorithm. This application is designed to be accessed online so that applicants can take intelligence tests anytime and anywhere. By using the latest security technology, applicant data security is guaranteed during the testing process. In addition, this application will provide test results automatically and present reports that are clear and easy to understand for companies. Through the application of the Test Intelligence application, it is hoped that companies can identify prospective employees who not only have technical qualifications, but also intelligence that matches the characteristics of the job being offered. Thus, this application is expected to make a positive contribution in increasing the efficiency and effectiveness of the recruitment process, ensuring appropriate employee selection, and ultimately improving company performance and productivity.